Dynamic Postural Stability of Old Tai Chi Practitioners During Obstacle-crossing - Li, Xiaolin (Université d'Ottawa / University of Ottawa, 2016)
Falls are the leading cause of injuries among Canadians who are aged at 65 years and over. The assessment of dynamic stability has been proved as an effective method to identify fall-prone elderly individuals, which is essential to fall prevention. Tai Chi has been recommended as an effective exercise to prevent falls by the American Geriatric Society and British Geriatric Society. It is important to examine dynamic stability among Tai Chi practitioners and to explore the mechanisms of the effects of Tai Chi practice on fall prevention. This study examined the dynamic postural stability which is assessed by center of mass (COM) range of motion, COM - center of pressure (COP) separation, and temporospacial measures of gait during obstacle-walking in two groups: Tai Chi group and healthy controls. Fifteen participants in each group were asked to complete two walking conditions, level walking and 20cm-obstacle walking. Results showed that when compared with Tai Chi group, control group adopted a conservative crossing strategy with a significantly smaller crossing stride, higher heel clearance, and smaller pre horizontal distance to make obstacle crossing as safe as possible. This conservative strategy indicates the inability to cross obstacle casually and it may be associated with the decline in muscle strength and proprioception. It also showed that Tai Chi practitioners displayed a significantly larger COM range of motion in both anteroposterior (AP) and mediolateral (ML) direction (p<0.05) and a significantly larger COM-COP separation in ML direction (p <0.01), as compared with control group. The larger range of motion of COM and distance between COM and COP indicates that Tai Chi practitioners have a better ability to tolerate unsteadiness, which means if perturbation occurs, Tai Chi practitioners have a larger range to shift COM in the boundary of base of support.
Keywords: Dynamic postural stability; TaiChi; obstacle crossing; blalance